(untitled) (International Journal of Biology and Chemistry, 2020)
The application of comparator instrumental neutron activation analysis combined with the internal standard method was considered to study rhenium content of the uranium raw material core samples collected in Chu-Sarysu uranium province in the Southern Kazakhstan. Iron content of the samples as the internal comparator was determined by X-ray fluorescence analysis with the help of a laboratory energy dispersive X-ray spectrometer. Rhenium was analyzed by its long-lived radionuclide 186Re using a planar type HPGe detector. Six certified reference materials of complex ores and non-ferrous metal concentrates were analyzed to verify the accuracy of the method. Rhenium and its main interfering elements were determined in the samples from three different sites of the uranium province. Due to reverse correlation dependence, selenium was found as a simple predictor of industrially significant rhenium contents. The method can be used to analyse rhenium mass fractions more than ≈0.02 ppm in the ores with uranium content of the samples not exceeding several hundreds ppm.